Multiscale finite element modelling of ductile damage behaviour of the human femur under dynamic loading. (April 2015) - Naceur, H; Rahmoun, J; Halgrin, J; Chabrand, P
In this paper, we propose a new multiscale finite element methodology based on a recently developed micromechanical damage model for the modelling of the human bone behaviour under dynamic loading. The damage is carried out by the framework of the limit analysis based on the MCK (Monchiet, Charkaluk and Kondo) criterion. We first present the methodology allowing the estimation of elastic anisotropic properties of porous media by means of Mori–Tanaka homogenisation scheme. Then, we develop the formulation of the integrated yield criterion derived by considering trial velocity field inspired from the Eshelby inhomogeneous inclusion solution. The obtained micromechanical model is implemented via a User Material routine within the explicit dynamic code LS-DYNA©. The proposed micromechanical model has been applied successfully for the estimation of the mechanical properties of a human proximal femur under dynamic loading. From the obtained numerical results, it has been shown that the present model has improved the strength prediction of osteoporotic femurs by representing the failure risk in a more realistic approach.